Relasi kuasa Islam dan Barat (Hubungan kekuasaan antara Islam dan Barat): Relationship of Islamic and West power (Power relations between Islamic and the West) - Taufik, Mohammad; Maarif, Zainul (JOURNAL OF GOVERNMENT SCIENCE, 2023)
This article examines the relationship between Islam and the West has a long and complex history. At certain times, these two civilizations collaborated and learned from each other, but at other times they were also involved in conflicts and wars. One of the biggest challenges of Islam and the West today is how they can build a more harmonious and understanding relationship. Dialogue is one way that can be done to achieve this goal. Dialogue can help both parties to understand each other's culture and values, thereby reducing understanding and conflict. Dialogue between Islam and the West is one of the important steps to build peace and prosperity in the world. With dialogue, the two communities can understand each other and work together to create a better world.